Measuring financial literacy: proposition of an instrument based on the Item Response Theory - Vieira, Kelmara Mendes; Moreira Júnior, Fernando de Jesus; Potrich, Ani Caroline Grigion (Ciência e Natura, 2020)
Financial literacy is a complex and multidimensional phenomenon. Thus, building a financial literacy measure has been a challenge. This study seeks to contribute to this scenario by proposing a Financial Literacy measure. The three dimensions suggested by the Organization for Economic Co-operation and Development (OECD) are considered: financial education, financial attitude and financial behavior. For validation of the measurement, the questions were constructed and the instrument was applied in 1576 Brazilians, between November and December 2013. To evaluate the measurement, two models of the Item Response Theory were used, the unidimensional two-parameter logistic model for the Financial Knowledge scale and the Graded Response Model (GRM) for financial attitude and behavior. From the main items, five levels of financial literacy were constructed. The results pointed to the appropriateness of the proposed measure. The final instrument has thirteen questions of financial knowledge, six of financial attitude and twenty-four of financial behavior, which allow to identify the level of individual financial literacy in each of the three dimensions. From the ability scales, we found that 44.10% of respondents had average financial knowledge. In the attitude and behavior scales, the most representative level was also the median (ability between -0.5 and 0.5).